Designing of anion‐functionalized ionic liquids for efficient capture of SO2 from flue gas. Issue 6 (27th March 2015) - Chen, Kaihong; Lin, Wenjun; Yu, Xini; Luo, Xiaoyan; Ding, Fang; He, Xi; Li, Haoran; Wang, Congmin
<x xml:space="preserve">Abstract</x> Five kinds of anion‐functionalized ionic liquids (ILs) with different basicity and substituent were selected, prepared and applied in the capture of SO2 from flue gas, where the concentration of SO2 is only 2000 ppm. The effect of the anion on SO2 absorption capacity, desorption residue, and available absorption capacity under 2000 ppm was investigated. The relationship between available absorption capacity and absorption enthalpy was also studied. Through a combination of thermodynamic analysis and quantum calculation, the results indicated that the effect of the cation in the IL on absorption enthalpy was significant. However, the effect of chain length in the cation was weak. Hence, a new IL with low molecular weight, [P4442][Tetz], was further designed and applied for the capture of SO2, which shows the high absorption capacity of 0.18 g SO2 per g IL and excellent reversibility for 2000 ppm SO2. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2028–2034, 2015